2022
DOI: 10.1039/d1fo03610f
|View full text |Cite
|
Sign up to set email alerts
|

10-Gingerol, a natural AMPK agonist, suppresses neointimal hyperplasia and inhibits vascular smooth muscle cell proliferation

Abstract: Background: Abnormal proliferation of vascular smooth muscle cells (VSMCs) in the intimal region is a key event in the development of neointimal hyperplasia. 10-G, a bioactive compound found in ginger,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that hypoxia can activate AMPK [15] and promote the proliferation and migration of VSMC [20,21]. However, other studies have shown that the activation of AMPK can inhibit VSMC proliferation and migration [22,23]. In this study, we have intuitively con rmed for the rst time that hypoxia can inhibit VSMC from climbing out of the edge of mouse aortic tissue blocks ex vivo, and promote VSMC phenotype regression by downregulating AMPK phosphorylation level.…”
Section: Discussionmentioning
confidence: 60%
“…Previous studies have shown that hypoxia can activate AMPK [15] and promote the proliferation and migration of VSMC [20,21]. However, other studies have shown that the activation of AMPK can inhibit VSMC proliferation and migration [22,23]. In this study, we have intuitively con rmed for the rst time that hypoxia can inhibit VSMC from climbing out of the edge of mouse aortic tissue blocks ex vivo, and promote VSMC phenotype regression by downregulating AMPK phosphorylation level.…”
Section: Discussionmentioning
confidence: 60%
“…The inclusion of the heterocyclic ring enhances 6-gingerol's ability to form hydrogen bonds. ( Tardibono and Miller, 2009 , Anzini et al, 2011 , Sahn et al, 2014 , Sampath et al, 2021 , Dalsasso et al, 2022 , Deng et al, 2022 ) Our objective is to offer a semi-synthetic method that is both straightforward and practical for the production of 1,4-benzodiazepines. By using 6-gingerol-derived 1-(4-hydroxy-3-methoxyphenyl)decane-3,5-dione, this technique entails the condensation of a variety of o-phenylenediamines, which is then followed by the cyclization of these compounds.…”
Section: Introductionmentioning
confidence: 99%